Structural and electrical properties of grain boundary Josephson Junctions based on Bi2Sr2CaCu2O8+d thin films (2000)
ABSTRACT: An in situ deposition sputtering process at high pressure has been developed for preparing high quality superconducting Bi2Sr2CaCu2O8+δ thin films on different substrates. Both microstructural and electrical properties were well characterized by TEM, AFM, RBS, X-ray diffraction, resistivity and magnetic susceptibility. The high reproducibility of the film quality facilitated a detailed study of Josephson effect in bicrystalline grain boundary junctions (GBJs). Thin films were deposited on (001) SrTiO3 bicrystals with misorientation angles of 24° and patterned by a photolithography process using Br-ethanol chemical etching. The width of the microbridges ranges from 10 to 50 μm. The critical current densities across the grain boundary have been measured and compared to the critical current in the film. A modulation in the critical current was found under magnetic field and also Shapiro steps in the I–V curves under microwave irradiation have been observed indicating a Josephson behavior. Electrical properties are well described by the resistively shunted junction (RSJ) model. The IcRn product reaches values around 2.0 mV at 4.2 K.